DOPUSZCZALNOŚć WIELOŚCI MIEJSC ZAMIESZKANIA W PRAWIE NIEMIECKIM. WZORCE HISTORYCZNE - Jurewicz, Aldona Rita (Zeszyty Prawnicze, 2016)
Permission for Multiple Places of Residence in German Law. Historical Patterns Summary The author uses a specific example, multiple residence under German law, to show the impact of Roman law on many of the modern European legal systems. The observations made by the editors of the German Bürgerliches Gesetzbuch (BGB) and the sources and literature they used show that Roman law was still relevant and universal in the 19th century, the age of the great codifications. Today, too, it is admissible under German law to have more than one residence and the issue is not controversial.